Effect of Calcium Channel Blockers on Antiplatelet Activity of Clopidogrel in Patients Undergoing Percutaneous Coronary Intervention: Insights from the PTRG-DES Consortium - HoungBeom Ahn MD; Hyun-Wook Chu MD; Ae-Young Her MD, PhD; Young-Hoon Jeong MD, PhD; Byeong-Keuk Kim MD, PhD; Hyung Joon Joo MD, PhD; Kiyuk Chang MD, PhD; Yongwhi Park MD, PhD; Sung Gyun Ahn MD, PhD; Sang Yeup Lee MD, PhD; Jung Rae Cho MD, PhD; Hyo-Soo Kim MD, PhD; et al. (SAGE Publishing, 2024)
Aims: Calcium channel blockers (CCBs) are frequently co-administered with clopidogrel in cardiovascular disease. Although an inhibitory drug interaction exists between them, comprehensive large-scale studies for its validation are lacking. We investigated interactions between CCBs and clopidogrel using a large-scale national registry of patients who underwent percutaneous coronary intervention (PCI). Methods and Results: The Platelet function and genoType-Related long-term Prognosis-Platelet Function Test consortium investigates the association between platelet function test and long-term prognosis during dual antiplatelet therapy including clopidogrel in patients using drug-eluting stents. We compared the ex vivo platelet reactivity using the VerifyNow P2Y12 test and clinical outcomes between CCB users and non-users. Between 2003 and 2018, 11 714 patients were enrolled and categorized into two groups according to CCB usage. A composite endpoint encompassing all-cause mortality, myocardial infarction, stent thrombosis, or stroke was defined as a major adverse cardiac and cerebrovascular event (MACCE). During the 5-year follow-up period, no significant differences were observed in P2Y12 reaction units (215.8 ± 84.7 vs 218.4 ± 76.7, P  = .156), MACCEs, major bleeding, or high platelet reactivity rates, even after adjusting for propensity score matching (PSM) and inverse probability of treatment weighting (IPTW). When limited to the high platelet reactivity cohort (≥252 PRU), the results remained consistent for MACCE [PSM-adjusted, HR: 0.923 (0.644-1.323), P -value .663; IPTW-adjusted, HR: 1.300 (0.822-2.056), P -value .262]. Conclusions: CCB and clopidogrel co-administration does not appear to significantly impact clopidogrel responsiveness or clinical outcomes. Despite these promising results, further investigation may be warranted. Clinical trial registration: Platelet Function and genoType-Related Long-term progGosis in DES-treated Patients: A Consortium From Multi-centered Registries [PTRG-DES]; NCT04734028